An exuberant case of necrobiotic xanthogranuloma - Sofia Lopes; Nuno Gomes; Artur César; Ana Margarida Barros; Jorge Pinheiro; Filomena Azevedo (Wolters Kluwer Medknow Publications, 2020)
Necrobiotic xanthogranuloma (NXG) is a rare form of inflammatory granulomatous disease of the skin characterized by the presence of pruritic to painful lesions, generally located in the periorbital area, although trunk and proximal extremities may also be involved. We report a case of a 69-year-old male patient with extensive involvement of the trunk, upper and lower extremities, and an associated gamma monoclonal gammopathy. The skin biopsy was consistent with the diagnosis of NXG. Necrobiosis lipoidica and granuloma annulare were the major differential diagnosis in this case. We highlight the importance of searching for clinical and histological features that may differentiate these entities, which is crucial to select an adequate therapeutic and surveillance strategy.